PENYELUNDUPAN IMIGRAN DI PERAIRAN INDONESIA DITINJAU DARI HUKUM INTERNASIONAL - Monica Kristiani Sitompul; Siti Muslimah; Anugrah Adiastuti (BELLI AC PACIS, 2015)
This research examined the problems regarding how the arrangement of immigrant smuggling on the sea based on UNCLOS 1982, the United Nations Convention against Transnational Organized Crime, and the Protocol against the Smuggling of Migrants by Land, Sea, and Air, supplementing the United Nations Convention against Transnational Organized Crime, and its uniformity to domestic law  also how Indonesia's obligations in dealing with immigrants who enter Indonesian waters by way of smuggled upon international law. This research was prescriptive normative law using secondary data types included primary and secondary legal materials. Data collection technique used literature studies which were analyzed with deductive method. The results showed that the arrangement immigrant smuggling on the sea that is based on the Act No. 6 of 2011 on Immigration, Act No. 6 of 1996 on Indonesian Waters, Government Regulation No. 36 of 2002 on the Rights and Obligations of Foreign Ships to Implement of Innocent Passage pass through Indonesian Waters and Government Regulation No. 37 of 2002 on the Rights and Obligations of Foreign Ships and Aircraft to Implement Right Through Islands Lanes Archipelagic Sea Lanes Defined already appropriate with UNCLOS in 1982, the United Nations Convention against Transnational Organized Crime, and Protocol against the Smuggling of Migrants by Land, Sea, and Air, supplementing the United Nations Convention against Transnational Organized Crime. Obligation to handling these immigrants, the Directorate General of Immigration is helped by international organizations, namely the IOM and UNHCR. The need fulfillment such as food, beverage, medical, and daily necessities is assisted by IOM while the determination of immigrants as refugees or not is decided by UNHCR, if the asylum application is rejected then the immigrant will be deported to their home country and then Directorate General of Immigration will taking care of official documents for the migrant reparation into their country.